Development and evaluation of lead(II) iodide-based polycrystalline digital dosimeter for quality assurance in brachytherapy. (16th November 2021) - Yang, S.W.; Han, M.J.; Park, S.K.
Abstract: Brachytherapy is a cancer treatment that involves intensively irradiating a tumor by placing a sealed radioactive isotope inside the body. Determining the position of the source through accurate quality assurance (QA) is important, because brachytherapy uses radioactive isotope sources with high dose rates. However, in clinical practice, the source position is determined with the naked eye through the use of a ruler, autoradiograph, video monitor, etc., which yields inaccurate results. Therefore, in this study, a lead (II) iodide (PbI2 ) based polycrystalline digital dosimeter that can measure the relative dose was developed for the QA of the brachytherapy device, and its applicability was evaluated in terms of reproducibility, linearity, percentage interval distance (PID), and angular dependence. Reproducibility evaluation yielded a relative standard deviation value of 1.41%, which satisfied the evaluation criterion of 1.5%. The linearity evaluation yielded an R 2 value of 0.9993, which satisfied the evaluation criterion of 0.9990. The PID evaluation revealed that, as the distance from the source increased, the signal decreased according to the inverse-square law. When the PbI2 -based digital dosimeter was rotated up to 45°, a difference of up to 13.20% in the angular dependence was observed. Thus, the dosimeter fabricated in this experiment met all the criteria of the aforementioned evaluations. Therefore, it is considered to be highly applicable as a dosimeter for the QA of brachytherapy devices.